Análisis de las prácticas comunicativas del Inti Raymi como sincronismo indígena – mestizo, enero-junio 2021 - Jhonatan Paúl, Orozco Colcha (2022)
RESUME The present research work analyzes the communicative practices of the Inti Raymi as an indigenous - mestizo synchronism that allows identifying the adaptation process emphasizing the coincidence of the two worlds from the ancestral celebration as a communicational process of identity and customs. Among the modernity that is lived now, validating the communication practices allowed to have a clear reference of the party and the message that it has in the Andean world with an important weight of gratitude to the land, understand the connection between the community and the Pacha Mama in addition to the food and meeting space. The Inti Raymi Festival is told from different actors, highlighting this celebration and asking for respect for the land, thanking the rain that wets the fields and where a planting time begins that will allow, above all, the safety of food on the table. . The spaces, rites, ceremonies are shown, the meeting between mestizos and indigenous people is inevitable, during these processes of communication, brotherhood and interaction between these two social groups there is an exchange of beliefs. From the theory of Cultural Anthropology, a celebration is held in the period arranged with an approach that allows data to be obtained through its culture and traditions, bringing customs and myths between beliefs closer together, as well as the value of this thanksgiving party with each one. of the details they have, the characters that participate in the rites that are behind in a video record. The types of research applied are descriptive when analyzing the Inti Raymi Festival and show its synchronism, and explanatory when deepening the aspects of the relationship between the indigenous and mestizo world. The type of methodology that is going to be used is the qualitative one when collecting information on the party as a process of social interaction in the places where it is fulfilled and the techniques of documentary review and interviews will be used. Gratitude is the beginning of a celebration that has a social, religious and cultural context, the Inti Raymi involves a series of processes that are carried out year after year and has a strong meaning and that clear message to Pacha Mama that means everything, abundance, food, health, workplace and meeting. It is transmitted to all generations with a performance of the indigenous population and in recent years even of the mestizo population that generates a process of communication and communicative practices that will be analyzed from the Inti Raymi and the value for being a connection of the human being with the nature, to evoke that symbiosis of connection that allowed millennial generations to build societies of development, progress and harmony. The present work allows observing the development of the Inti Raymi celebration as well as describing how the communicative practices in the Inti Raymi generate a synchronism between indigenous and mestizos that allow establishing other discourses and reflections and ends with a video about what the communicative practices are. that are presented in the celebration of the Inti Raymi. KEY WORDS: Communication, Inti Raymi, Synchronism